(untitled) - Fabris-Rotelli, Inger Nicolette

Spatial linear network Voronoi analysis to quantify accessibility of police stations in South Africa (University of Pretoria, 2025)
Mini Dissertation (MSc (Advanced Data Analytics))--University of Pretoria, 2024.